Gingival fibroma versus verrucous leukoplakia – A clinical dilemma!!! - Renu Garg; Manoj Margabandhu; Ajish Paul; Kennedy Babu (Journal of Indian Society of Periodontology, 2016)
Gingival overgrowths found in the oral cavity are mostly due to reactive hyperplasia and rarely depict neoplastic nature. It is a challenge for the clinician to give final diagnoses of gingival overgrowth. Gingiva is a common site for various benign and malignant lesions. Oral cavity is an ideal niche for the manifestation of various precancerous and cancerous lesions. Fibrous growths present in the oral cavity include a varying group of reactive, precancerous, and cancerous conditions. This report describes a case of a 55-year-old male who clinically presented with a localized fibromatous gingival overgrowth in relation to lower left mandibular canine-premolar region that was diagnosed as a gingival fibroma associated with leukoplakia. On histopathological examination, it was diagnosed as a case of proliferative verrucous leukoplakia. Many a times, clinicians face dilemma while diagnosing an overgrowth as it is difficult to differentiate clinically. Hence, a thorough clinical knowledge and a pathologist's opinion become mandatory to give final diagnosis to such gingival overgrowths.